Religion and governance: new typology, a philosophical inquiry - Malik, Maszlee (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
In post-modern times there has been much empirical evidence to indicate that religions and faiths play a pro-active role in the civil society; more importantly in the development of societies, which is a major factor in the development of a country, as well as its governance . Religion as a form of ethical doctrine could potentially provide the ‘internal good’ for development through its doctrines on social cohesion, mutual co-operation and virtue-based community. In practice, the process of governance is not an axiological neutral human activity, but like other activities, it is impregnated with values and ethics . Consequently, apart from mainstream liberal economic ethics (i.e. efficiency, competitiveness, economic growth, human rights, etc.) there are other traditional, culturally-constructed and religious ethics that are worth incorporating into the discourse in order to respond to the realities of each society for it to reach an acceptable and efficient solution for itself. It is through this premise that the Aristotelian concept of praxis is worth employing to explain how ethics and tradition can encourage a society to cooperate to attain telos (internal goods).